2015
DOI: 10.1128/jvi.03188-14
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors Block Multiple Functions of the NS3/4A Protease-Helicase during the Hepatitis C Virus Life Cycle

Abstract: Hepatitis C virus (HCV) NS3 is a multifunctional protein composed of a protease domain and a helicase domain linked by a flexible linker. Protease activity is required to generate viral nonstructural (NS) proteins involved in RNA replication. Helicase activity is required for RNA replication, and genetic evidence implicates the helicase domain in virus assembly. Binding of protease inhibitors (PIs) to the protease active site blocks NS3-dependent polyprotein processing but might impact other steps of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…In H77S.3, telaprevir blocked replication and assembly (85). We showed that boceprevir inhibited replication across genotypes, and paritaprevir and grazoprevir inhibited genotype 2a (isolate JFH1) replication.…”
Section: Discussionmentioning
confidence: 89%
“…In H77S.3, telaprevir blocked replication and assembly (85). We showed that boceprevir inhibited replication across genotypes, and paritaprevir and grazoprevir inhibited genotype 2a (isolate JFH1) replication.…”
Section: Discussionmentioning
confidence: 89%
“…43 Interestingly, the predictions that NS5A inhibitors and protease inhibitors affect both viral replication and virion assembly and secretion are now supported by in vitro experiments. 43,46,47 Furthermore, IFN has been shown to rapidly affect infectious particle genesis. 48 …”
Section: Modelling Ifn-based Therapymentioning
confidence: 99%
“…Recent studies showed that HCV NS3/4A attenuated innate immunity by blocking DDX58 signaling and MVAS protein cleavage. 36,37 To the best of our knowledge, this is the first study on the association between DDX58 rs9695310 and HCV infection in Chinese Han population.…”
Section: Discussionmentioning
confidence: 88%